STUDI PENYEBAB TERJADINYA BANJIR DI KAWASAN PERMUKIMAN KELURAHANSUNGAI SAPIH KECAMATAN KURANJIKOTA PADANG - Firdayanti, Sri - (STKIP PGRI Sumbar, 2014)
The purposes of this this study to determine the cause of the flooding that reviewed from rainfall, drainage, topography and types of rock in settlement areas ,Sungai Sapih village, Sub-District Kuranji , Padang City.The type of this research is descriptive research that leads to disclosure of the facts and analysis needed from the result of observations in the field. The sample selection of this study using purposive sampling method so that be obtained two regions for the study samples that are Kurao Kapalo Banda and Aie Paku because this area is an area that is frequently hit by floods at the Sungai Sapih village.The result of the study found that in regions of Kurao Kapalo Banda and Aie Paku have rainfall 230,3 mm/month and 3901 mm/year. The drainage in Kurao Kapalo Banda area is rather hampered that is seen from a length of 9 km, width 66 cm, depth 45 cm and travel time 54 sec / m, whereas in Aie Paku area the drainage is hampered that is seen from a length of 7 km, width 37 cm, depth 17 cm and travel time 81 sec / m. The topography in Kurao Kapalo Banda area 15 miles from the sea surface, the slope of 4%, whereas in Aie Paku area 11 miles from the sea surface, the slope of 3% so both of these areas are the plains. Based on the discovery in the field and topography map the type of rock in regions of Kurao Kapalo Banda and Aie Paku is classified the alluvium (Qal) with the characteristics of clay deposits, sand and gravel. Based on the results of the study it can be concluded that the flooding in Kurao Kapalo Banda area is classified high and the flooding in Aie Paku is classified very high.